The main factors and prospects for the restoration of biodiversity in technogenic territories (on the example of the Poltava Mining and Processing Plant) - Chaplygina, А. B.; Filatova, О. V.; Litvin, L. М.; Nykyforov, V. V. (My University, 2023)
Мета статті: Провести уніфікованими методами аналіз успішності відновлення біорізноманіття, інвентаризацію видів флори вищих рослин та орнітофауни техногенних територій Полтавського гірничо-збагачувального комбінату (ПГЗК). Дослідження проводились у весняно-літній період 2021-2022 років. Детально вивчено домінуючі види, виявлені у гірничих відвалах, хвостосховищах, обвідних і дренажних каналах, міських очисних і біоінженерних спорудах та на території ПМЗ. У демутаційних сукцесіях виявлено загальні закономірності: біогеоценози, що оточують техногенні території ПГЗК, є основним джерелом діаспор і різноманітних консументів, які так необхідні для відновлення деградованих ландшафтів. Фанерофіти з родів Populus, Pinus, Fraxinus, Ulmus, Morus, Juglans визначають домінування в орнітокомплексах дендрофілів, характерні для сусідніх соснових і заплавних лісів, садів та території приватної забудови.Успішність природного формування рослинних угруповань, багатий орнітологічний комплекс за участю рідкісних видів, розташування території ПГЗК в межах міграційних шляхів свідчать про доцільність подальших досліджень можливостей їх включення до природно-заповідного фонду з статусом «територія ренатуралізації». To conduct an analysis of the success of restoring biodiversity, an inventory of species of flora of higher plants and avifauna of man-made territories of the Poltava Mining and Processing Plant (PGZK) using unified methods. The studies were carried out in the spring-summer period of 2021-2022. The dominant species identified in mining dumps, tailings, bypass and drainage canals, urban wastewater treatment and bioengineering facilities and on the PMP territory have been studied in detail.In demutational successions, general patterns were revealed: biogeocenoses surrounding the technogenic territories of PMP are the main source of producer diasporas and a variety of consumers, which are so necessary for the restoration of degraded landscapes. Phanerophytes from the genera Populus, Pinus, Fraxinus, Ulmus, Morus, Juglans, etc. are determinants in the sylvacenoses formed on the dumps and territories of the plant. Therefore, dendrophiles characteristic of neighboring pine and floodplain forests, as well as garden phytocenoses in the territory of private development, dominate in the ornithocomplexes. The success of the natural formation of plant communities, the rich ornithological complex with the participation of rare species, and the location of the PMP territory within the migration routes indicate the expediency of further research into the possibilities of their inclusion in the natural reserve fund with the status of «territory of renaturalization».
The main factors and prospects for the restoration of biodiversity in technogenic territories (on the example of the Poltava Mining and Processing Plant) / А. B. Chaplygina, О. V. Filatova, L. М. Litvin, V. V. Nykyforov // Biosystems Diversity, 2023. – № 31(1). – Р. 100-112
Keywords: флора судинних рослин, орнітофауна, видобуток корисних копалин, сукцесії, біологічне різноманіття, рідкісні види; flora of vascular plants, avifauna, mining, successions, biological diversity, rare species